Pengembangan Aplikasi Ojek Daring untuk Motor Ramah Difabel (Toradi) berbasis Android - Amira Fauzia Rahmah; Ismiarta Aknuranda; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The provision of accessibility of public facilities is necessary to realize equal rights for people with disabilities. To fulfill this, the Research and Community Service Agency of the Faculty of Medicine, University of Brawijaya proposes the Disability-Friendly Motorcycles (Toradi) project. Toradi is a motorcycle that has been modified by adding a sidecar that functions as a pillion and is designed to be easily accessed by people with disabilities. They also want Toradi to become an online transportation business because so far people with disabilities have experienced difficulties when using online transportation services that are already available. The difficulty is due to drivers who often refuse orders when they know their condition. Therefore in this research, an Android-based online transportation application will be built which can connect the disabled people with Toradi and making it easier for them to do mobility. The application development uses a prototyping method that helps developers to explore system requirements more easily. The application was developed using the Kotlin programming language with an object-oriented approach. Then the application is tested with functional testing and compatibility testing. Functional test results indicate that the application is valid. The compatibility test results show the application can run on Android devices with a version above 5. Furthermore, the application is evaluated by the user based on the system acceptance criteria and gets a value of 93.6% which can be concluded that the application can be well received by the user.